PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SDN 06 PONTIANAK - Santiya, Santi; setyaningrum, saumi; Yapandi, Yapandi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
This reseach so that students have not been able to maximize the picture and picture learning model so that the ability of students to increase students' learning motivation and improve learning outcomes to the fullest. The purpose of this study was to (1) determine the learning outcomes of students before and after using the picture and picture learning model on the learning outcomes of students on animal metamorphosis. (2) Knowing student learning outcomes after using the picture and picture learning model on student learning outcomes for animal metamorphosis for class IV SDN 06 East Pontianak in 2021/2022. To achieve this goal, this research uses quantitative methods with experimental types. The conclusions of this study (1) The learning outcomes of students before using the picture and picture learning model (pretest) have obtained an overall average value of 62.86 with sufficient categories. This result has not reached the Minimum Completeness Criteria (KKM) which is 75 in animal metamorphosis material. (2) The learning outcomes of students after using the picture and picture learning model (posttest) increased with an average value of 81.07 with a good category on animal metamorphosis material.